Pembuatan Sanggul Modern dari Sabut Kelapa sebagai Peluang Usaha - Diah Ayu Maulina; Agus Susanti; Nurulisma Saputri (Garina, 2024)
Making a modern bun from coconut fiber to support your appearance can be an idea for a business opportunity because the coconut fiber fiber material does not require too much additional material, so the price of a modern bun from coconut fiber is relatively cheaper. The aim of this research is to find out and explain the process of making a modern bun from coconut fiber, validate the modern bun from coconut fiber, and the public's acceptance of the modern bun from coconut fiber. Data collection uses the methods of observation, literature, experiments, documentation, interviews, questionnaires, and data analysis using descriptive qualitative. The sensory test results from 3 coloring trials on the bun were declared valid on product 3 with a total average color of 4.5, a total average texture of 4.3, a total average of packaging of 4.5, while the total the average aroma is 4.1. The results of the public test showed that people's acceptance was at the highest level of liking in experiment 3 with an average total of 4.5 colors, a texture of 4.3, an average total of packaging of 4.5 while an average total of aroma of 4.1. From the research results, making modern buns from coconut fiber is quite good, creative and innovative, so it can be a business opportunity.